2016
DOI: 10.1590/1806-9282.62.07.691
|View full text |Cite
|
Sign up to set email alerts
|

Adult T-cell leukemia/lymphoma

Abstract: Adult t-cell leukemiA/lymphomA rev assoC med bras 2016; 62 (7):691-700 691

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 69 publications
0
21
0
3
Order By: Relevance
“…ATLL is an aggressive T‐cell proliferation which is developed in the infected individuals after a lengthy latency period. The leukemic cells are monoclonal and mostly displayed the immunophenotype of CD2+/CD3+/CD4+/CD5+/CD7‐/CD8‐/CD20‐/CD79a‐/CD25+ . HAM/TSP mainly targets the neuro­logic cells and causes the increase in the expression level of some cytokines, adhesion molecules, Fas/Fas ligand, and molecules impressing T cell migration in the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…ATLL is an aggressive T‐cell proliferation which is developed in the infected individuals after a lengthy latency period. The leukemic cells are monoclonal and mostly displayed the immunophenotype of CD2+/CD3+/CD4+/CD5+/CD7‐/CD8‐/CD20‐/CD79a‐/CD25+ . HAM/TSP mainly targets the neuro­logic cells and causes the increase in the expression level of some cytokines, adhesion molecules, Fas/Fas ligand, and molecules impressing T cell migration in the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This action could contribute to control HTLV replication. Although initial observations suggested that the synthesis of 1,25(OH) 2 D and PTHrP by HTLV-infected lymphocytes in patients with ATL was associated with hypercalcemia, the main cause of death in patients with ATL, subsequent studies failed to show increased levels of 1,25(OH) 2 D and PTHrP [38,41]. A prospective study of subjects admitted to a hematology unit evaluated the incidence of hypercalcemia and the association with humoral mechanisms involving PTHrP, parathyroid hormone (PTH) and 1,25(OH) 2 D. Hypercalcemia was detected in few subjects and was caused by primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the immune response in HTLV pathogenesis is not fully understood, but the efficacy of the individual immune response defines the control or limitation of viral persistence and, ultimately, the outcome of HTLVassociated diseases [34 -37]. HTLV can immortalize human lymphocytes, specially TCD4 + lymphocytes in ATL [38].…”
Section: Introductionmentioning
confidence: 99%
“…CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) regimen cen be used with 25% CRR. Hyper-CVAD (cyclophospha mide, vincristine, doxorubicin, and dexamethasone-meth otrexate, cytarabine) is acceptable as an alternative regimen [21]. Combination of Zidovudine and IFN-α shown to be effective in the leukemic subtypes in a meta-analysis.…”
Section: Adult T Cell Leukemia/lymphomamentioning
confidence: 99%